The education of art culture at Sultanate of Oman through the multidisciplinary integration between graphic design and eco-friendly textile printing. Part 1: Standardization of extraction and dyeing with natural wastes products. (February 2020) - Mansour, H.; Hilal, N.; Alhajri, S.; Al-Yahyai, F.; Al-Amri, M.
Abstract: Scientific research today is marked by a growing differentiation and specialization in the disciplines and interdisciplinary research. This paper investigates a number of challenges of Interdisciplinary collaborations in implementation of a circular economy approach within textile and graphic designs. These challenges range from achieving economy of scale required for commercial viability and finding secondary markets for the recycled materials to developing 'resource efficient recycling processes' that are especially tailored to the specific needs of eco-friendly textile products. Art Education Department at Sultan Qaboos University created interdisciplinary education strategy through an artistic relevant, and engaging the textile printing and graphic design courses in a project. The aim of this project is to apply some natural waste products which contain pigments to be served as recycling sources for natural dyes in textile coloration regarding their increasing interest due to their biodegradability and environmental awareness. The research project was divided in two parts; part one depends on studying the optimum condition of extraction with different co-solvent on different textile fabrics, as the extraction can be an energy, economic and environmental friendly by waste recycling. Part two deals on studying the mixing of the resulted extractions in producing a variety of hues under the effect of different pH values, mordants and mordanting methods to promote artistic printed textile patterns assisted by the graphic design. Therefore, students are introduced to different and integrated ways of thinking, aiming to make them more aware of circular economy and sustainability issues in all of their art activities, from personal to professional environments. As a result, this research is considered as a double scientific leap in terms of development strategies for teaching art curricula through the Multidisciplinary Integration in serving the community and the environment.